E-Book Development at Kebonsari III Elementary School Tuban City - Anggun Winata; Ifa Seftia Rahkma Widiyanti; Saeful Mizan; Sri Cacik (UNUSA Press, 2021)
Information and Communication Technology (ICT) in education is one of the main supporters of educational services through the development of e-books. The purpose of this activity is to increase teacher competence in utilizing ICT to prepare the 21st century education system in facing the industrial revolution 4.0. This activity uses the community development method through training, mentoring and development in the preparation of e-book learning media. Instrument achievement of implementation indicators using pretest and posttest questionnaires for knowledge and skills of e-book development for teachers at Analysis of the results of achievement using descriptive analysis of the average value and percentage. The average pretest results of participants' abilities in developing e-books are still less visible from the results of less than 11%, very less by 77%, enough by 6%, good 4% and very good by 2% . The average posttest results of participants' ability in developing e-books increased, namely very less and less by 0%, enough by 26%, good by 60% and very good by 14%. The community development method is able to increase the knowledge and skills of teachers in developing e-book learning media